The Effectiveness of Disaster Management Policies in Reducing the Impact of Natural Disasters in Canada - Samuel, Ethan (Journal of Public Policy and Administration, 2024)
Purpose: To aim of the study was to analyze the effectiveness of disaster management policies in reducing the impact of natural disasters. Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: The effectiveness of disaster management policies in reducing the impact of natural disasters largely depends on several key factors: early warning systems, community preparedness, infrastructure resilience, and coordinated response efforts. Studies indicate that well-implemented policies that prioritize risk assessment, public education, and resource allocation significantly mitigate the damage and loss of life during natural disasters. Unique Contribution to Theory, Practice and Policy: Systems theory, social capital theory & vulnerability theory may be used to anchor future studies on the effectiveness of disaster management policies in reducing the impact of natural disasters. Implementing practices that strengthen social capital within communities is essential. Policies should be designed to address the specific vulnerabilities of different population groups. This includes tailoring disaster management strategies to the needs of marginalized communities, women, children, the elderly, and people with disabilities.